METHODS OF ASSESSING THE CURRENT STATE OF EQUIPMENT QUALIFICATION IN UKRAINIAN NPPS - Остапенко, Иван Анатольевич; Горанчук, Денис Викторович; Косяк, Дмитрий Николаевич (Eastern-European Journal of Enterprise Technologies, 2012)
Purpose - Development and optimization of the overall scheme of equipment qualification. The paper presents an optimized scheme of the process and discussed the main aspects of qualification. The decision methods are offered.